2015
DOI: 10.1016/b978-0-444-59428-0.00010-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Inequality and Poverty in Developing Countries

Abstract: This chapter reviews the empirical evidence on the levels and trends in income/consumption inequality and poverty in developing countries. It includes a discussion of data sources and measurement issues, evidence on the levels of inequality and poverty across countries and regions, an assessment of trends in these variables since the early 1980s, and a general discussion of their determinants. There has been tremendous progress in the measurement of inequality and poverty in the developing world, although seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 120 publications
(140 reference statements)
7
65
0
9
Order By: Relevance
“…Recent comparisons of Gini coefficients on household consumption per capita calculated for developing regions do confirm that the median Gini is higher in Latin America and the Caribbean, although the mean Gini is slightly lower than in sub-Saharan Africa (Alvaredo and Gasparini 2015). In any case, the levels of inequality are high for almost every country in the region, and undoubtedly inequality is a persistent characteristic of LAC.…”
Section: Recent Evolution Of Income Inequality In Latin Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent comparisons of Gini coefficients on household consumption per capita calculated for developing regions do confirm that the median Gini is higher in Latin America and the Caribbean, although the mean Gini is slightly lower than in sub-Saharan Africa (Alvaredo and Gasparini 2015). In any case, the levels of inequality are high for almost every country in the region, and undoubtedly inequality is a persistent characteristic of LAC.…”
Section: Recent Evolution Of Income Inequality In Latin Americamentioning
confidence: 99%
“…Annex (see Table A.1) Alvaredo and Gasparini (2015) Open Access This chapter is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, a link is provided to the Creative Commons license and indicate if changes were made. The images or other third party material in this chapter are included in the work's Creative Commons license, unless indicated otherwise in the credit line; if such material is not included in the work's Creative Commons license and the respective action is not permitted by statutory regulation, users will need to obtain permission from the license holder to duplicate, adapt or reproduce the material.…”
Section: Final Remarksmentioning
confidence: 99%
“…En cualquier caso, también se calcularon los indicadores de desigualdad sin ajuste y los resultados obtenidos son siempre robustos. Por último, se definió un mínimo de subsistencia de 300 dólares anuales, consistente con el utilizado por Milanovic, Lindert y Williamson (2011). 14 América Latina y el Caribe típicamente son señaladas como las regiones más desiguales del mundo, pero este tipo de afirmación usualmente se hace combinando Ginis de ingreso con Ginis de consumo para el resto de las regiones o ignorando la región de África subsahariana (Alvaredo y Gasparini, 2014). Como se observará a continuación, incluso realizando los ajustes pertinentes, América Latina es una de las regiones con mayor desigualdad.…”
Section: Gráfica 4 Tasa De Extracción E Ingreso Promedio a Lo Largo unclassified
“…During the last decade, Latin America has experienced an important decrease in household income inequality (Lustig et al 2013;Alvaredo and Gasparini 2015). Recent studies have shown that the main driver must have been the reduction in wage inequality (Abad and Lindert 2017;De la Torre et al 2017).…”
Section: Introductionmentioning
confidence: 99%